PERANAN INVESTASI DALAM MENUNJANG PEMBANGUNAN PEREKONOMIAN DI INDONESIA - Irmawaty Ambo (Maleo Law Journal, 2018)
The legal role in the national development effort is expected to not only play a role as a legitimator of the implementation of development results but also as a direction in the implementation of national development. Investment policy is a tool to attract investors (investors) to invest their capital in Indonesia. The owner of the capital can come from within the country or can also come from abroad (foreign). However, the need for foreign investment is special, and therefore attracting foreign investment must be done in a special way, given the intense competition with other countries. So the legal, institutional and incentive system must be built as well as possible so that Indonesia becomes an attractive investment destination. practical, investment factors can be used as one of the main instruments or factors to spur and enhance economic growth. Furthermore, investment policies are expected to be a stimulant for increasing work for the community. So there is a linear and sustainable relationship between investment and economic growth and employment opportunities for the community. The most frequent complaint made by foreign investors so far is that there are so many types of licensing that must be obtained, which directly makes the initial cost to swell up before the company is inflated. operate.Kata Kunci : Investation. Development